2004
DOI: 10.1056/nejmoa041365
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Renal Dysfunction and Cardiovascular Outcomes after Myocardial Infarction

Abstract: Even mild renal disease, as assessed by the estimated GFR, should be considered a major risk factor for cardiovascular complications after a myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

43
874
8
30

Year Published

2005
2005
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,700 publications
(955 citation statements)
references
References 39 publications
43
874
8
30
Order By: Relevance
“…[1][2][3][4][5] In addition to the underlying primary pathological state, several factors, such as lifestyle, socioeconomic status (SES), and occupational exposures, were suggested to modify the progression and outcome of kidney diseases and may be responsible, in part, for the disproportionately high rates of end-stage renal disease in such subgroups as racial/ethnic minorities. [6][7][8][9][10] African Americans were reported to have greater rates of proteinuria.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] In addition to the underlying primary pathological state, several factors, such as lifestyle, socioeconomic status (SES), and occupational exposures, were suggested to modify the progression and outcome of kidney diseases and may be responsible, in part, for the disproportionately high rates of end-stage renal disease in such subgroups as racial/ethnic minorities. [6][7][8][9][10] African Americans were reported to have greater rates of proteinuria.…”
mentioning
confidence: 99%
“…A number of studies have reported the prognostic significance of eGFR in patients with CAD; [11][12][13][14][15][16][17][18] however, the majority of these studies were in Western countries and GFR was estimated by the MDRD equation or by creatinine clearance. Reports from Asian countries are very limited, possibly because of the lack of an accurate equation for eGFR in Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in which the prevalence of patients with eGFR o60 ml min À1 per 1.73 m 2 (that is, chronic kidney disease stage X3, according to the clinical guideline 21 ) was investigated in patients with CAD, showed that the prevalence of patients with eGFR o60 ml min À1 per 1.73 m 2 was 16-46% in Western countries. 11,12,[15][16][17][18] The MDRD equation or creatinine clearance was used in the majority of these studies. On the other hand, the prevalence of patients with eGFR o60 ml min À1 per 1.73 m 2 in Japanese patients with CAD was reported as 35 and 39% (Inaguma et al 13 and Furukawa et al 14 ) using MDRD equation with Japanese coefficient or creatinine clearance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 High-risk patients, such as those with left ventricular dysfunction, have lower ejection fractions and higher New York Heart Association (NYHA) class when accompanied by impaired renal function. 8 Recently published data have reported the increased risk of CV disease once the glomerular filtration rate (GFR) dropped below 60 ml/min/1.73m 2 in patients at high CV risk 16 and the general population. 17 In combination, these data demonstrate that renal dysfunction imparts significant risk for CV disease.…”
Section: Discussionmentioning
confidence: 99%